The Effect of the Utilization of a Preprinted Protocol for the Use of Intravenous Pantoprazole on Its Appropriate Administration - Majid Iranshahi; Rezvan Hassanpour; Mohammad Sistanizad; Habib Malekpour; Arezoo Ashnagar; Elham Pourheidar (Tehran University of Medical Sciences, 2022)
Background: Proton pump inhibitors (PPIs) are the most effective medications in acid-related disorders. Inappropriate use of Intravenous (IV) pantoprazole can cause unwanted consequences like hypersensitivity reactions, prolonged duration of treatment, and increased treatment cost. This study aimed to evaluate the effect of the utilization of a preprinted protocol for the use of IV pantoprazole on its appropriate administration. Methode: This prospective, cross-sectional, two-phase study was conducted on the four departments of a tertiary teaching hospital. In the first phase, December 22, 2018, to March 19, 2019, all older than 18-year old patients who were admitted to internal medicine, general surgery, and neurosurgery, and received IV pantoprazole were included in the study. In the second phase of the study, April 4, 2019, to July 6, 2019, the neurology ward was added to the study according to the high consumption of IV pantoprazole. We evaluated the effect of the utilization of a preprinted protocol for the appropriate of IV pantoprazole on its consumption, and the frequency of appropriate administration based on the approved protocol, the need to change the patient's medication regimen, and the physician's feedback on the changes. The consumption of IV pantoprazole was compared with the same period times at the last year of intervention as the pre-intervention phases. Results: Four hundred forty-six prescriptions of IV pantoprazole were screened during the 2 phases of the study. The utilization of the approved protocol consequent decrease in IV pantoprazole consumption in intervention phases compared with pre-intervention phases in all departments. This difference was statistically significant in the general surgery  (p= 0.016) and neurosurgery (p= 0.012) wards in phase 2. Related data to the comparison of the IV pantoprazole consumption between two phases of the intervention also showed a significant decrease in the neurosurgery ward (p= 0.011). In the total of the two phases, the use of the protocol led to an 8.3% decrease in consumption in comparison with pre-intervention periods. During these six months, we detected that the administration of IV pantoprazole was not based on the protocol in 81.2% of patients and the use of the protocol led to correct 63.89% of physician's orders. Conclusion: This study showed that the majority of IV pantoprazole prescriptions were inappropriate. Using the preprinted forms to administer the IV pantoprazole could improve its appropriateness in terms of indication for use, dose, and duration of treatment and decrease consumption.